Anticancer activity of Astragalus ovinus against 7, 12 dimethyl benz (a) anthracene (DMBA)-induced breast cancer in rats - Fouad Mehraban; Mostafa Mostafazadeh; Hossein Sadeghi; Arsalan Azizi; Mehdi Akbartabar Touri; Bita Gramizadeh; Vahid Barati; Heibatollah Sadeghi (Mashhad University of Medical Sciences, 2020)
Objective: Some species of Astragalus are used for the treatment of various types of cancer. The present study was designed to evaluate the anticancer potential of Astragalus ovinus extract (AOE) against DMBA-induced breast carcinoma in rats. Materials and Methods: The anti-tumor and antioxidant effects of AOE were evaluated against DMBA-induced breast carcinoma in rats using DPPH, FRAP and ABTS technique, respectively. Forty adult female Sprague-Dawley rats were randomly divided into four groups including the control group received a single dose of DMBA solvent orally, and groups II, III and IV received a single dose of DMBA (40 mg/kg) dissolved in olive oil. Groups I and II received normal saline and groups III and IV were treated with AOE orally (120 and 240 mg/kg respectively) for 60 consecutive days. Chemopreventive effects were assessed in terms of diameter and volume of tumors, expression levels of PCNA, and serum levels of CA15.3, p53, MDA, CAT, and calcium, and histopathological features Results: AOE contained a noticeable amount of phenolic and flavonoids compounds. This extract showed a potent antioxidant activity both in vitro and in vivo. AOE significantly decreased the diameter and volume of tumors (p<0.01) and reduced the serum levels of CA15.3 (p<0.001), p53 (p<0.01), MDA (p<0.001), and calcium (p<0.01). AOE also decreased the expression of PCNA in cancerous tissues and reduced the histopathological deformity. Conclusion: According to the data, AOE produced a significant chemopreventive activity in DMBA-induced breast tumors in rats, probably due to its antioxidant and its inhibitory effect on some tumorigenicity markers such as CA15.3, p53 and PCNA activity.